Derivatives of Sums

Example:
z = (q2 - 8)-5 - q7

The first thing to notice when finding the derivative of this function is that it is the sum of several terms, as shown in color below:

z = ( (q2 - 8)-5 ) - ( q7 )

The Derivative Rule for Sums:

The derivative of a sum is the sum of the derivatives.
If
  z = ( f(x) + g(x) )
then the derivative of z is
  z' = ( f(x) + g(x) )'
    = f '(x) + g'(x)

So our example,

z = ( (q2 - 8)-5 ) - ( q7 )
we can think of as
z = f(q) - g(q)
So the derivative is
z ' = ( f(q) - g(q) )'
  = f '(q) - g '(q)  
  = ( (q2 - 8)-5) ' - ( q7) '  
and we just need to know each of the derivatives on the right-hand side of the equation. In this case these are
( (q2 - 8)-5 )' = (-5)*(q2 - 8)-6 (2*q - 0) (by the chain rule)
( q7 )' = 7*q6 (by the power rule)
so the finished derivative is
z ' = (-5)*(q2 - 8)-6 (2*q - 0) - 7*q6  
  = (-10)*q (q2 - 8)-6 - 7*q6
[]


additional explanation for the derivative of sums
see another derivative of sums example
practice gateway test
previous page
Page Generated: Thu Feb 6 21:00:47 2025
Comments to Gavin LaRose
glarose@umich.edu
©2001 Gavin LaRose, University of Michigan Math Dept.